The Concept of the Duty Obedience - Amer A. Abu-nayla (Journal of Madenat Alelem University College, 2015)
The research topic focuses for a question that if the employee should implement all orders issued from his boss without discussion or objection, veto or debate and to what extent or what are the limits of this debate? Several theories have appeared in this regard. The first theory which is the oldest one requires the employee to carry out orders issued to him by his boss without any objection. The theory gave the rationale for this view. After that, an alternative theory emerged and gave an enough room for discussion and deliberation. The holders of these theoretical opinion strengthened unrealistic methods and evidence. And then a third theory emerged as an intermediate between the two previous theories, states that the employee should inform his boss that the issued order has been merged with a legal error and could not be implemented. If the boss insisted on his opinion editorially, the employee has to implement the command and the boss holds out the legal responsibility arising from it. Iraqi legislator has taken the law in the discipline of state employees in this direction. This research would attempt to clarify this in detail.